Customer Satisfaction with Service Quality, Pricing and Promotion Approaches - Irawan, Muhammad Hari; Gemina, Dwi; Palahudin (MultiTech Publisher, 2024)
This research aims to determine and analyze the influence of service quality, price and promotion on consumer satisfaction, both simultaneously and partially. This research design uses descriptive, verification and path analysis research methods. The sampling technique uses the saturated sampling method. The number of respondents was 100 people. The subjects of this research are Bogor Punya Kopi consumers, and the research objects are service quality, price, promotion and consumer satisfaction. The tools used in this analysis are path analysis, multiple correlation analysis, coefficient of determination analysis, and hypothesis testing (F test and t test). The results of the analysis show that partially or simultaneously service quality, price and promotion have a direct and positive influence on consumer satisfaction at the Bogor Punya Kopi cafe.